Os impactos das relações de poder sobre as mulheres nas famílias: histórias de vidas femininas em Fortaleza - Campelo, Maria Helena Rodrigues (2019)
The object of study of the present Master's Dissertation in Brazilian Education of the Federal University of Ceará - UFC constitutes: the impacts of power relations on women in families: stories of women's lives in Fortaleza. Interest in this area originated in my own personal life histories and in the history of professional daily life, in academic formation, in the experiences and experiences of dialogue with other women that inspired the desire to tell the stories of their families. The general objective is to analyze the impacts of power relations on women in families, based on female narratives in Fortaleza. As specific objectives we aim: to identify the expressions of the relations of power in the families, through the contradictions and complexities; understand the implications of power relations on the reality of women, through their process of subjectivation; to observe the interactions between power relations and the constitution of the identity and social representation of women. The starting question was: how do power relations impact women in families? We consider as hypothesis: women are impacted in their families due to power relations, expressed as inequalities between men and women in families. As a methodology, we used the theoretical references of Cultural History, the perspective of comparison of Comparative History, the techniques of Oral History the type of research was configured as qualitative and bibliographical. The theoretical references used correspond: Foucault (1988); Beauvoir (2009); Perrot (2007); Priore (2015); Ariés (1986); Scott (1989); among others. We indicate as results: the transformations in the family models affected the roles and social functions of women, because they interfere in the symbolic dimension and in the process of subjectivation; education aimed at women reinforced gender inequality, overwhelmed women in relation to family, domestic and professional life, hindering the process of freedom, autonomy, empowerment and female protagonism. As final considerations, we indicate: the study on the history of women permeates the understanding about the history of families and of all humanity.